Effectiveness of Brief In-person and Virtual Substance Use Disorder Counselor Trainings, 2019-2021. (May 2023) - Cambron, Christopher; Castillo, Jason T.; Frost, Caren J.
Objectives: Paraprofessional substance use disorder counselors (SUDCs) are an important component of expanding access to substance use disorder treatment, but little research on SUDC training currently exists. We evaluated knowledge and self-efficacy gain from brief in-person and virtual workshops for paraprofessional SUDC student-trainees. Methods: Student-trainees (N = 100) enrolled in an undergraduate SUDC training program completed 6 brief workshops from April 2019 to April 2021. Three in-person workshops during 2019 covered clinical assessment, suicide risk and evaluation, and motivational interviewing, and 3 virtual workshops during 2020-2021 covered family engagement and mindfulness-oriented recovery enhancement, as well as screening, brief intervention, and referral to treatment for expectant mothers. Pretest and posttest online surveys measured student-trainee knowledge gain related to all 6 SUDC modalities. Results of paired sample t tests evaluated changes in knowledge and self-efficacy from pretest to posttest. Results: All 6 workshops showed a significant gain in knowledge from pretest to posttest. Four workshops showed a significant gain in self-efficacy from pretest to posttest. Hedges g ranged from 0.70 to 1.95 for knowledge gain and from 0.61 to 1.73 for self-efficacy gain across workshops. Common language effect sizes indicating the probability that a participant increased one's score from pretest to posttest ranged from 76% to 93% for knowledge gain and from 73% to 97% for self-efficacy gain across workshops. Conclusions: Results of this study add to the limited research base on training for paraprofessional SUDCs and suggest that in-person learning and virtual learning are both viable brief training tools for students.